1983
DOI: 10.1017/s0022172400028886
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and level of contamination of British fresh sausages and ingredients with salmonellas

Abstract: SUMMARYA five-tube most probable number (MPN) method, with pre-enrichment and enrichment stages, was used in a study ofthe incidence ofsalmonella contamination of British fresh sausages and the ingredients used in their manufacture. All samples were taken from a large factory in the course of routine production. There was an incidence of 65 % contamination of pork (n = 20) and 55 % (n = 20) in pork and beef sausages. The incidences of contamination of uncooked ingredients varied from 95 % for mechanically reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…However, they differ considerably in relation to S. derby, which was never isolated in our survey despite its frequent occurrence in swine (3,8,19) and pork products (2,9). In our study, S. cholerae-suis was isolated only twice, one strain belonging to the kunzendorf(monophasic variety) and the other one to the america type (biphasic variety); such a relatively low frequency seems to be in accordance with other investigations from different parts of the world (5,19).…”
Section: T H E V E T E Rcontrasting
confidence: 55%
“…However, they differ considerably in relation to S. derby, which was never isolated in our survey despite its frequent occurrence in swine (3,8,19) and pork products (2,9). In our study, S. cholerae-suis was isolated only twice, one strain belonging to the kunzendorf(monophasic variety) and the other one to the america type (biphasic variety); such a relatively low frequency seems to be in accordance with other investigations from different parts of the world (5,19).…”
Section: T H E V E T E Rcontrasting
confidence: 55%
“…In view of their accurate taxonomic delineation, Enterobacteriacea may be regarded as suitable for this purpose . Recently Gerats et al, (1981) and Banks & Board (1983) have demonstrated that for pig carcasses and sausage meat a certain relationship exists between mesophilic Enterobacteriaceae colony counts and the extent of Salmonella contamination. Figure 1, redrawn from Gerats et al (1981), illustrates this point.…”
Section: Experimental Partmentioning
confidence: 99%
“…Salmonella Derby has also been frequently associated with pork in many countries (Chau and Shortridge 1977; Liow and Loh 1977; Barrell 1982, Barrell 1987; El‐Nawani et al . 1982; Banks and Board 1983; Currier et al . 1986; Jayarao et al .…”
Section: Discussionmentioning
confidence: 99%